THEORETICAL FOUNDATIONS OF ORGANIZING MEDIA EDUCATION IN THE FIELD OF PRESCHOOL EDUCATION (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
Media education plays an important role in the process of preschool education by developing children's media literacy and their ability to correctly perceive information. This article explores the theoretical foundations of organizing media education for preschool-aged children. The main principles, methodological approaches, and pedagogical significance of media education are analyzed. Additionally, recommendations are provided for the effective implementation of media education in preschool institutions.